1999
DOI: 10.1111/j.1745-4573.1999.tb00387.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Postmortem Skeletal Alterations Effect on Sarcomere Length, Myofibrillar Fragmentation, and Muscle Tenderness of Beef From Light‐weight, Brangus Heifers

Abstract: Approximately 2 h after exsanguination, two skeletal cuts (TC) were made on randomly selected sides from 13 light‐weight, Brangus heifers; companion sides served as untreated controls (C). After a 24‐h chill period, four muscles (Longissimus muscle from the IMPS#112A ribeye roll, LT, and from the IMPS#180 strip loin, LL; Biceps femoris, BF; Semitendinosus, ST; and Semimembranosus, SM) were excised from each side, vacuum‐packaged, and aged for 7 days. Five 2.54‐cm thick steaks were cut from each of the muscles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
3

Year Published

2001
2001
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 25 publications
3
14
3
Order By: Relevance
“…However, the relative increase in sarcomere length from skeletal cuts in the present study was much lower than previous findings Ludwig et al 1997) evaluating steer and heifer carcasses altered at the 12th/13th vertebrae. The effect on sarcomere length from skeletal cuts in the present study is similar to those found by Beaty et al (1999) who applied skeletal cuts to the thoracic vertebra and pelvic bone, while exceeding the increases in sarcomere length in the posterior longissimus lumborum from severing the 6th thoracic and 5th lumbar vertebrae (Aalhus et al 1999). Sarcomere length in the loin eye was greater (P < 0.04) with separation at the 12/13th site as compared with the 11/12th site.…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations
“…However, the relative increase in sarcomere length from skeletal cuts in the present study was much lower than previous findings Ludwig et al 1997) evaluating steer and heifer carcasses altered at the 12th/13th vertebrae. The effect on sarcomere length from skeletal cuts in the present study is similar to those found by Beaty et al (1999) who applied skeletal cuts to the thoracic vertebra and pelvic bone, while exceeding the increases in sarcomere length in the posterior longissimus lumborum from severing the 6th thoracic and 5th lumbar vertebrae (Aalhus et al 1999). Sarcomere length in the loin eye was greater (P < 0.04) with separation at the 12/13th site as compared with the 11/12th site.…”
Section: Resultssupporting
confidence: 77%
“…Shear force in the posterior loin was not affected (P = 0.69) by skeletal separation (Table 2), which is in contrast to previous studies where shear force was decreased in the longissimus lumborum when skeletal cuts were made between the 12th/13th vertebrae with additional cuts to the pelvic bone (Aalhus et al 1999;Beaty et al 1999). However, Ludwig et al (1997) found a nonsignificant decrease in shear force when the Tendercut process was applied to the posterior loin.…”
Section: Resultscontrasting
confidence: 55%
See 2 more Smart Citations
“…The main advantage over tenderstretch is that the sides are conventionally hung. Results to date suggest that Tendercut is an effective means for improving tenderness (Wang et al 1994(Wang et al , 1996Beatty et al 1999) in commercially valuable hindquarter muscles.…”
Section: Alternative Carcass Suspensionmentioning
confidence: 99%